The Determinant of Takaful Acceptance: Theory of Reasoned Action Approach - Hasyim, Fuad (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
Indonesia has great potential for Islamic insurance (takaful) based on the ratio of GDP. But still very few Indonesians, who have used Islamic insurance as a form of risk management and financial planning. This can be seen from the data, Indonesia has low literacy index and financial inclusion, mainly on conventional insurance (15.8% literacy, 12.1% inclusion) and Islamic insurance (2.51% literacy, 1.92 inclusions). This study aims to reveal why the low of Islamic insurance acceptance in Indonesia. This research uses a quantitative method, using the Theory of Reasoned Action Approach (TRA). The TRA construct identifies the effect of Attitude and Subjective Norms on Behavior through Intention. TRA constructs can be measured using the Structural Equation Modeling method with Partial Least Square (SEM-PLS). The results found that acceptance of Islamic insurance is influenced by attitude and subjective norms. Technically, either directly or indirectly, attitude variables affect the behavior through intention (sig. 0,000) or subjective norms variable affect to behavior through intention (Sig. 0,003